Polyimides cross‐linked with amino group‐containing compounds. Issue 12 (4th February 2017) - Sysel, P.; Maly, D.; Vysohlid, J.; Friess, K.; Pilnacek, K.; Lanc, M.; Vopicka, O.
Abstract : The commercially available linear polyimide Matrimid ® 9725 was crosslinked with amino groups containing both high‐molecular‐weight and low‐molecular‐weight compounds. The multi‐functional amine‐terminated hyperbranched polyimide precursor (hyperbranched polyamic acid), based on 4, 4′‐(hexafluoroisopropylidene)diphthalic anhydride and 4, 4′, 4″‐triaminotriphenylmethane, and its fully imidized form (amine‐terminated hyperbranched polyimide), bifunctional amine, 4, 4′‐diaminodiphenylamine and trifunctional amine, 4, 4′, 4″‐triaminotriphenylamine, were used as the crosslinkers. Theoretically, 10% or 20% of the Matrimid imide groups was reacted with the amino groups of the crosslinking agent during the formation of the amide groups. The insoluble content (gel) in the final materials was very low at the crosslinking temperature of 80°C and was in the 55–90% range at the crosslinking temperature of 200°. The permeability coefficients of hydrogen, carbon dioxide and methane in the self‐standing, mechanically tough film (membrane) based on the combination of Matrimid and hyperbranched polyimide were approximately 30–45% higher compared with those in the membrane made of pure Matrimid at a comparable separating ability (selectivity). POLYM. ENG. SCI., 57:1367–1373, 2017. © 2017 Society of Plastics Engineers